Multiple cholangiocarcinomas in the intrahepatic and extrahepatic biliary tree due to dichloromethane exposure: a case report - Daisuke Ogawa; Hiromitsu Hayashi; Fumimasa Kitamura; Norio Uemura; Tatsunori Miyata; Hirohisa Okabe; Katsunori Imai; Yoichi Yamasita; Shoji Kubo; Hideo Baba (Surgical Case Reports)
Abstract Background An outbreak of cholangiocarcinoma in Japan has led to widespread concern among workers in printing plants. In March 2013, the Japanese Ministry of Health, Labour and Welfare, confirmed a causal relationship between cholangiocarcinoma and long-term exposure to dichloromethane (DCM) and 1,2-dichloropropane (DCP), which were widely used in printing plants. We herein report a rare case of successful radical resection of multiple cholangiocarcinomas in the intrahepatic and extrahepatic bile ducts caused by past exposure to DCM. Case presentation A 54-year-old man developed brown urine 22 years after his last exposure to DCP and DCM. He had an 11-year history of working at a printing plant from the age of 21 to 31 years and dealt with organic solvents during his employment. Enhanced computed tomography revealed a thickened distal bile duct wall with upstream biliary dilatation and multiple intrahepatic cholangiocarcinomas located in liver segments III, VI, and VIII. Biopsy of the distal bile duct wall revealed adenocarcinoma, and a diagnosis of distal cholangiocarcinoma was made. Tumor marker levels were within the reference range (carcinoembryonic antigen, 3.3 ng/mL; carbohydrate antigen 19-9, 25.4 U/mL; SPAN-1, 13 U/mL; and DUPAN-2, 33 U/mL). The multiple intrahepatic and extrahepatic bile duct cancers were treated by subtotal stomach-preserving pancreatoduodenectomy and partial hepatectomy of segments III, VI, and VIII. Pathological examination of the surgical specimens revealed multiple cholangiocarcinomas with well-differentiated adenocarcinoma in the biliary tree. The patient was still alive without recurrence 17 months after the operation. Conclusions We experienced a rare case of multiple cholangiocarcinomas in the intrahepatic and extrahepatic bile ducts that developed 22 years after the patient’s last exposure to DCP and DCM. Long-term and careful follow-up is required for workers with an occupational history of exposure to organic solvents because of the risk of development of cholangiocarcinoma.